Effect of the association of garlic (Allium sativum L.) and onion (Allium cepa L.) in the production of maracuya (Passiflora edulis Sims.) during the seedling stage - Camilo Alexander, Mestanza Uquillas (2021)
For an adequate production of passion fruit, it is essential to use quality seed and obtain seedlings free of pests and diseases, which provide the favorable conditions for their growth during the initial stage of development. Based on this antecedent, the effect of the association of passion fruit (Passiflora edulis) + onion (Allium cepa) + garlic (Allium sativum) was evaluated, in two different substrates: Without disinfection and Disinfected. A completely randomized experimental design was applied with a bifactorial arrangement (2 type of soil x 2 cultivation system), generating four interactions: Without disinfection-Only, Without disinfection-Associated, Disinfected-Only and Disinfected-Associated, arranged in four repetitions. Sowing was carried out in 2 m2 plantations under field conditions. The results for germination and dead plants showed significant differences (P<0.05) for the treatments of associated systems at 15 and 50 days after sowing. Regarding the agronomic behavior, the interactions of associated systems could show a positive response in the variables of plant height, fresh aerial and radical weight, aerial and radical biomass. Nitrogen, phosphorus, potassium, and sulfur levels were increased to adequate levels. The association of passion fruit and species of the genus Allium benefit the production of seedlings by improving the survival, development and nutrition of the plant and the soil.